Raising the level of physical fitness as one of the program tasks implemented during a scout camp - Kowalska, Anastazja (Journal of Education, Health and Sport, 2022)
The article presents the results of the own research carried out during the scout colonies in July 2022. The research included an examination of the following: whether and to what extent the level of physical fitness of 24 children aged 7-10, participating in program activities carried out during the recreation, increased during the two-week scout camps in Rusinowo (at the Polish seaside). The following research hypothesis was set: It is hypothesized that during a scout camp, children will raise their level of physical fitness in all tests. Based on the results presented, it was found that the children did not raise their level of physical fitness in all competitions of the test. In most of the trials, the results of the second measurement were better, while results worse than in the first measurement were also noted. Therefore, it should be concluded that the research hypothesis set was not confirmed. However, during the study, differences were observed due to the gender of the children, with a predominance of better results in girls.